Antiparasitic bromotyrosine derivatives from the marine sponge Verongula rigida (2011)
ABSTARCT: Nine bromotyrosine-derived compounds were isolated from the Caribbean marine sponge Verongula rigida. Two of them, aeroplysinin-1 (1) and dihydroxyaerothionin (2), are known compounds for this species, and the other seven are unknown compounds for this species, namely: 3,5-dibromo-N,N,N-trimethyltyraminium (3), 3,5-dibromo-N,N,N, O-tetramethyltyraminium (4), purealidin R (5), 19-deoxyfistularin 3 (6), purealidin B (7), 11-hydroxyaerothionin (8) and fistularin-3 (9). Structural determination of the isolated compounds was performed using one- and two-dimensional NMR, MS and other spectroscopy data. All isolated compounds were screened for their in vitro activity against three parasitic protozoa: Leishmania panamensis, Plasmodium falciparum and Trypanosoma cruzi. Compounds 7 and 8 showed selective antiparasitic activity at 10 and 5 μM against Leishmania and Plasmodium parasites, respectively. Cytotoxicity of these compounds on a human promonocytic cell line was also assessed.